2021
DOI: 10.4236/asm.2021.114005
|View full text |Cite
|
Sign up to set email alerts
|

Sperm Quality and Environment: A Retrospective, Cohort Study among 21,715 Semen Samples in a Southern Province of China

Abstract: To explore the differences of male semen parameters in different seasons of the year, so as to explore the potential climatic factors affecting spermatogenesis and male reproductive ability, we retrospectively analyzed 21,715 semen analysis data from January 2018 to February 2021, grouped by year and season, and finally the relationships among semen parameters and semen and meteorological parameters were compared. Environmental exposures prior to 3 months were analyzed and correlation analysis was performed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…We found that temperature and apparent temperature correlated negatively with semen quality, what is in line with previous results. [ 15 , 34 ] Moreover, for sperm concentration, TSC and TMSC, an increase in the rates of abnormalities and a decrease in the mean values were found in summer, in comparison to winter. In addition, patients exposed to the highest values of temperature and apparent temperature (Q4 group) showed a poorer semen quality.…”
Section: Discussionmentioning
confidence: 98%
“…We found that temperature and apparent temperature correlated negatively with semen quality, what is in line with previous results. [ 15 , 34 ] Moreover, for sperm concentration, TSC and TMSC, an increase in the rates of abnormalities and a decrease in the mean values were found in summer, in comparison to winter. In addition, patients exposed to the highest values of temperature and apparent temperature (Q4 group) showed a poorer semen quality.…”
Section: Discussionmentioning
confidence: 98%